Farewell, Grandpa Elephant : a picture book story about death - Abedi, Isabel, 1967- (Skyhorse Pub., 2012)
When Grandpa Elephant tells his grandchildren that he is going to the elephant graveyard to die, the children have many questions for him about death and what comes next.